Proteomic profiling dataset of chemical perturbations in multiple biological backgrounds - Deborah O. Dele-Oni; Karen E. Christianson; Shawn B. Egri; Alvaro Sebastian Vaca Jacome; Katherine C. DeRuff; James Mullahoo; Vagisha Sharma; Desiree Davison; Tak Ko; Michael Bula; Joel Blanchard; Jennie Z. Young; et al. (Scientific Data, 2021)
Measurement(s) drug perturbation response Technology Type(s) proteomic profiling Factor Type(s) cell line • drug Sample Characteristic - Organism Homo sapiens Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14744064